Analisis Efektivitas Kondensor Di PLTU PT. Semen Tonasa Btg Unit I 2×25 MW - Jamal Chandra Bhuana; Irfan Muh; Aqsha Maulana (PoliGrid, 2021)
Abstract: This research was conducted to determine the effect of fouling on the effectiveness of condensers in the Steam Power Plant (PLTU) PT. Semen Tonasa. The research method used is data collection in the central control room PLTU PT. Semen Tonasa. Steam temperature inlet condenser (Thin), temperature of condensate water  (Thout), steam pressure inlet condenser (Ps), pressure of cooling water (Pcw), inlet temperature (Tcin) and outlet temperature of cooling water (Tcout), steam flow rate ( and cooling water flow rate () is the data needed in this research. Data were analyzed to get the value of effectiveness, number transfer of units (NTU), capacity ratio (C), log mean temperature different (LMTD) of the condenser. The results of the analysis showed that the decrease in condenser performance was influenced by the effect of fouling. Overhaul is done every 2 years. There was a decrease in NTU's value of 31.69% and an effective value of 22.29% in the period April 2016 to March 2018.